Moving into and out of high-performance sport: the cultural learning of an artistic gymnast - Barker-Ruchti, N.; Schubring, A. (Physical Education and Sport Pedagogy, 2016)
Background: High-performance sport has been described as a formative environment through which athletes learn sporting skills but also develop athletic selves. Within this process, career movements related to selection for and de-selection from representative teams constitute critical moments. Further, retirement from sport can be problematic as the athletic self becomes `obsolete`. This dilemma is acute in sports that demand an early entry, extreme time investments and a high risk of retirement before adulthood. Women's artistic gymnastics (WAG) is such a sport.